FETOMATERNAL OUTCOME IN WOMEN WITH OLIGOHYDRAMNIOS INDUCED WITH MISOPROSTOL - Amir, Fouzia; Ara, Gulshan; Basharat, Ayesha; Amir, Shazia (Journal of Ayub Medical College Abbottabad, 2019)
Background: Oligohydramnios, defined as an amniotic fluid index (AFI) of less than the 5th percentile (at term ‰¤5 cm, or at per-term ‰¤8.0 cm), has an incidence of 8.5-15.5%. It is associated with an increased perinatal morbidity and mortality. The objective of this study was to explore whether induction with misoprostol can safely be offered to patients with reduced amniotic fluid index and that vaginal delivery can be achieved without major adverse effects. Method: All women at term who gave consent to be part of the study and required labour induction were recruited. Total 120 women were included in study. They had a per-induction ultrasound to calculate amniotic fluid index (AFI). Based on AFI., the patients were divided into two groups: group 1, had AFI ‰¤5 cm and was oligohydramnios group. The other was group 2 with normal amniotic fluid, i.e., AFI >5 cm. Both these groups then underwent labour induction with misoprostol (cytotec-Pfizer) 50microgram. The dose was repeated 6 hourly for a maximum of three doses. The outcomes studied were number of tablets used, induction to labour interval, induction to the delivery interval and method of delivery. The foetal outcomes were meconium staining, Apgar score, NICU admission and advance neonatal resuscitation. Results: In maternal parameters, it was observed that there was a significant difference in induction to delivery interval only and in foetal parameters it was observed that in group 1, there was statistical significance in meconium staining, Apgar score and NICU admission. Conclusion: Induction with misoprostol and vaginal delivery can safely be offered to women with oligohydramnios at term. Keywords: misoprostol; induction of labour; oligohydramnios